Penerapan Model Eliciting Activities (MEAs) dalam Pembelajaran Matematika Materi Relasi dan Fungsi - Melia Kartika; Cecil Hiltrimartin (Universitas Maritim Raja Ali Haji, 2019)
This study is the descriptive research that aims to determine student learning activities when applied MEAs approach and learning outcomes after applied MEAs with subject relation and function. The subjects were students of class VIIID junior high school number 1 Indralaya Utara, amounting to 32 students. The data were collected using observation dan test and analyzed descriptively. The research result to shows the implementation of student learning on the MEAs approach included in the good category. From result learning get 29% students included in the very active category, 19% students included in active category and 26% students included in quite an active category while students learning outcomes included pretty good when 7% students included in very good category, 33% students included in good category and 40% students included in pretty good category, with an average value is 66,1.